Large-scale production of paper-based Li-ion cells - Zolin, Lorenzo (Springer, 2016)
This book describes in detail the use of natural cellulose fibers for the production of innovative, low-cost, and easily recyclable lithium-ion (Li-ion) cells by means of fast and reliable papermaking procedures that employ water as a solvent. In addition, it proposes specific methods to optimize the safety features of these paper-based cells and to improve the electronic conductivity of the electrodes by means of a carbonization process- an interesting novel technology that enables higher current rate capabilities to be achieved. The in-depth descriptions of materials, methods, and techniques are complemented by the inclusion of a general overview of electrochemical devices and, in particular, of different Li-ion battery configurations. Presenting the outcomes of this important research, the work is of wide interest to electrochemical engineers in both research institutions and industry.- Resumé vydavatel
Keywords: lithium-iontové baterie; materiály; elektrochemie; lithium-ion batteries; materials; electrochemistry; elektronické knihy; monografie; electronic books; monographs